The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1021/bc034075e
|View full text |Cite
|
Sign up to set email alerts
|

No Enhancement of Nuclear Entry by Direct Conjugation of a Nuclear Localization Signal Peptide to Linearized DNA

Abstract: Efficient nuclear entry of exogenous DNA is one of the key factors toward gene therapy success with nonviral vectors. To re-address the effects of a nuclear localization signal (NLS) peptide attached directly to DNA, we prepared three dumbbell-shaped, green fluorescent protein (GFP)-encoding DNAs containing one or two NLS peptides. The peptide was conjugated to the loop-forming oligodeoxyribonucleotides by cross-linking reactions between the peptide and a modified uracil base with a dioxaoctylamino linker, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 17 publications
3
54
0
Order By: Relevance
“…The reports indicated that the combination of G4-PAMAM dendrimer with glucocorticoid dexamethasone (PAM-Dex) facilitates the nuclear translocation of polymer/pDNA complex and increases pDNA delivery in Neuro2A cells more than two-fold and six-fold as compared to PEI and PAMAM alone, respectively 121 . The studies also demonstrated that the modification of polymers with multifunctional peptides drives the DNA from the lysosome to the nucleus 122,123 .…”
Section: Biopolymersmentioning
confidence: 99%
“…The reports indicated that the combination of G4-PAMAM dendrimer with glucocorticoid dexamethasone (PAM-Dex) facilitates the nuclear translocation of polymer/pDNA complex and increases pDNA delivery in Neuro2A cells more than two-fold and six-fold as compared to PEI and PAMAM alone, respectively 121 . The studies also demonstrated that the modification of polymers with multifunctional peptides drives the DNA from the lysosome to the nucleus 122,123 .…”
Section: Biopolymersmentioning
confidence: 99%
“…In an initial trial, the NLS was directly conjugated to DNA. However, nuclear delivery efficacy is not enhanced drastically, even when 1 or 2 NLS was chemically conjugated to the linearized DNA [53,54]. Thus, modification of the pDNA with proteins (i.e.…”
Section: Control Of the Intracellular Trafficking For Pdna Deliverymentioning
confidence: 99%
“…For instance, coupling of streptavidin-NLS conjugates to biotinylated DNA enabled linear DNA fragments to enter the nuclear of digitonin-permealized cells by an active transport process. 23 Increases in gene expression has also been observed following ligation of an oligonucleotide-NLS conjugate to one or both terminal to a linear DNA molecule. 6 Conjugation of the NLS peptide to the N3-position of adenine bases in double-stranded DNA yielded no increase in the nuclear uptake of the modified DNA or transgene expression.…”
Section: Introductionmentioning
confidence: 99%